2021
DOI: 10.1093/rheumatology/keaa909
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of abnormal BMI to adverse health-related quality of life outcomes after a 52-week therapy in patients with SLE

Abstract: Objectives To investigate whether abnormal BMI is associated with adverse health-related quality of life (HRQoL) outcome, including severe fatigue, after 52 weeks of standard therapy plus belimumab or placebo in patients with SLE. Methods We analysed data from the BLISS-52 (NCT00424476) and BLISS-76 (NCT00410384) trials (n = 1684). Adverse HRQoL was defined as SF-36 scores ≤ the fifth percentile in age- and sex-matched US pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…Herein, we investigated frequencies of adverse HRQoL outcome and contributing factors in 760 patients with SLE who showed adequate clinical response to a 52-week long intervention with standard therapy along with belimumab or placebo, using previously reported definitions (30). We observed clinically important diminutions of patient-reported HRQoL in multiple physical, mental and social aspects compared with the general population, and high frequencies of adverse HRQoL outcomes, especially within physical domains of SF-36 and FACIT-F.…”
Section: Discussionmentioning
confidence: 97%
“…Herein, we investigated frequencies of adverse HRQoL outcome and contributing factors in 760 patients with SLE who showed adequate clinical response to a 52-week long intervention with standard therapy along with belimumab or placebo, using previously reported definitions (30). We observed clinically important diminutions of patient-reported HRQoL in multiple physical, mental and social aspects compared with the general population, and high frequencies of adverse HRQoL outcomes, especially within physical domains of SF-36 and FACIT-F.…”
Section: Discussionmentioning
confidence: 97%
“…For example, an estimate of 0.5 means that five consecutive visits in LLDAS are required to reach a 2.5 difference in the median PCS or MCS, while an estimate of 0.1 would require 25 visits. All models were adjusted for age, sex, ethnicity, country, belimumab treatment, antimalarial treatment, immunosuppressive agents, disease duration, BMI, and organ damage (SDI score), all considered factors with confounding potentiality based on previous research [ 3 , 35 , 36 ] ( Supplementary Table S2 , available at Rheumatology online). We also tested for the interaction term between belimumab use and remission/LLDAS; as no significant interaction was noted other than in one single model (exposure: remission; outcome: SF-36 PCS), the term was excluded from the final models.…”
Section: Methodsmentioning
confidence: 99%
“…In general, when evaluating the impact of the health problems studied in SLE patients, there was a lack of consideration and adjustment for socioeconomic factors [ 28 ]. Socioeconomic data are often easy to obtain, but researchers should be aware of their importance as they may modify the impact of obesity, diabetes mellitus, and cardiovascular risk in underserved SLE patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that there are certain measures of burden that have been poorly evaluated in recent literature, such as the burden of treatment, disability, health care utilization, work participation, and, clearly, economic burden [ 13 , 28 ]. Most studies to date that have attempted to assess the impact of obesity and diabetes on the health outcomes of SLE patients have a cross-sectional design, so causality cannot be inferred [ 15 , 19 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%